Pedagogia antirracista junto a uma turma da educação infantil na cidade de São Carlos: processos educativos decorrentes - Oliveira, Alessandra Guerra da Silva (2024)
We understand children as autonomous, active subjects, protagonists who produce cultures in all the social relationships and practices they experience. From this perspective, the objective of this study was to understand the educational processes resulting from dialogical and anti-racist pedagogical practices, in an intervention based on and for the Education of Ethnic-Racial Relations, together with children in a reference Early Childhood Education class in the city of São Carlos, through experiences involving games, games and conversation circles, observing Law 10.639/2003 (Brazil, 2003) which made the Teaching of African and Afro-Brazilian History and Culture mandatory, of the National Curricular Guidelines for the Education of Ethnic- Racial (Brazil, 2004), as well as Resolution CME 005/2009, of the Municipal Education Council of the city of São Carlos (São Carlos, 2009). The study methodology was qualitative, inspired by phenomenology, with the data collection procedure being systematic records of observations in field diaries. When constructing the results, we established the following categories: A) Being more and feeling welcomed in differences; B) Educate and educate yourself in and for the Education of Ethnic-Racial Relations; C) Affection, memories and ancestry. We consider that knowing and recognizing oneself in African and Afro-Brazilian history and culture, positive self-esteem, valuing hair, respect for differences, the feeling of ethnic-racial belonging, appreciation and pride in ancestry, were being built in the collective, establishing themselves as educational processes. We highlight that the continuity of anti-racist pedagogical practices, throughout the year, collaborative work (children, family members, teachers), with continued teacher training enhance the actions carried out that seek more humanizing practices and enhance the learning of our children. Joint actions that make us reflect on the importance of a new school and society project, in which the union of all instances and people from different segments is crucial, so that respect and acceptance of differences are present in pedagogical practices, curricula school and public policies.